THE EQUATION OF RIBA AND INTEREST - Hasriadi, Hasriadi (Universitas Islam Negeri Alauddin Makassar, 2021)
Riba is a part of economic activity that has been developing since the era of jahiliyah until now. This interest-based lending and borrowing system is very beneficial for capital owners and on the other hand has plunged the poor into destitution. Therefore, Islam prohibits the practice of riba and fosters the shadaqah tradition so that no one is persecuted due to riba. The issue of the similarity between the practice of riba and usury which is forbidden in the Qur'an and the hadith is difficult to refute when viewed from the size of the harm it causes. However, the understanding of the Muslim community towards the concept of riba and its equality is not evenly distributed, so that many Muslims still converge with conventional banks that use the interest system in all aspects of their lives, including in collecting funds for the pilgrimage. Therefore, the author will describe the meaning of riba, the types of practice in today's life by using an approach and analysis of the sources of Islamic teachings.